THE INTERACTION BETWEEN DEVELOPMENT OF STRENGTH AND OTHER DRIVING SKILLS IN HANDBALL - Florin-Valentin Leuciuc (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The handball game is in constant change and evolution, with a permanent and dynamic acceleration, so that work to improve physical training must be done systematically and consistently throughout the sport activity. Specific physical training aims to ensure the qualities necessary for players to cope with the distinct game requirements that requesting speed, strength, coordinative capacity and stamina. The necessity to identify new components was felt especially in sports performance that lately has reached very high rates, pushing the limits of human body possibilities.